Rural Residents’ Perspectives on Multiple Morbidity Management and Disease Prevention - Bardach, Shoshana H. (2011)
Middle-aged and older adults often experience several simultaneously occurring chronic conditions or “multiple morbidity” (MM). The task of both managing MM and preventing chronic conditions can be overwhelming, particularly in populations with high disease burdens, low socioeconomic status, and health care provider shortages. This article sought to understand Appalachian residents’ perspectives on MM management and prevention. Forty-one rural Appalachian residents aged 50 and above with MM were interviewed about disease management and colorectal cancer (CRC) prevention. Transcripts were examined for overall analytic categories and coded using techniques to enhance transferability and rigor. Participants indicate facing various challenges to prevention due, in part, to conditions within their rural environment. Patients and providers spend significant time and energy on MM management, often precluding prevention activities. This article discusses implications of MM management for CRC prevention and strategies to increase disease prevention among this rural, vulnerable population burdened by MM.